A rare case of enamel pearl in canine tooth - Mariz, Ana Carolina Ramos; Brito, Gabriela Meyge de; Farias, Daniela Adorno; Machado, André Wilson; Campos, Paulo Sérgio Flores (Journal of Oral Diagnosis, 2019)
The enamel pearl (EP) is a dental developmental anomaly that usually manifests in furcation areas, and is uncommon in uniradicular teeth. We present a case of EP on the vestibular surface of tooth 13 in a 38-year-old patient, who was submitted to multislice computed tomography (MSCT) for orthognathic surgery planning. The attenuation coefficient (3.070 HU) allowed the condition to be classified as a true EP.